Immunoreactive Factor VIII in Carriers of Hemophilia A+ and A- - Lechner, K (Thrombosis and Haemostasis, 1973)
Factor VIII activity and inhibitor-neutralizing capacity of plasmas of 30 probable or definite carriers of hemophilia A were compared. The inhibitor-neutralization test is less useful to recognize the carrier-state than the factor VIII assay. Plasmas of two carriers belonging to families (in which, in at least one member, the diagnosis of hemophilia A+ was established) had an inhibitor neutralizing capacity twice as high as expected from the biological activity, while 28 carriers from hemophilia A- families had an inhibitor neutralizing-capacity equivalent to their factor VIII activity.